Kompetensi Pedagogik Guru Pendidikan Agama Islam dalam Meningkatkan Keaktifan Belajar Peserta Didik di Sekolah Menengah Pertama Negeri 22 BatangHari : Pedagogical Competencies of Islamic Religious Education Teachers in Increasing Students' Learning Activeness in State Junior High Schools 22 Batang Hari - Arsul, Ariza; Suharni; Husni, Radhiatul (CV. Kalimasada Group, 2024)
The purpose of this study was to determine the learning strategies used by instructors of Islamic Religious Education (PAI) in SMPN 22 Batang Hari in order to increase student engagement. It also aims to pinpoint the challenges educators face when encouraging engaged student engagement in the classroom. In this study, descriptive qualitative methodology was used, and information was collected through documentation, interviews, and observations. PAI students, educators, principals, and teachers participated in the study. Data collection, reduction, presentation, and conclusion or verification are steps in the data analysis process. The findings show that although teachers have used pedagogical competence to encourage students ' learning activities, they have not yet reached their full potential. Lesson planning, subject mastery, and understanding of student characteristics all show evidence of an effective approach. However, as traditional teaching methods continue to be the primary means used to deliver lessons, there is still room for development in the integration of Learning media.